PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS FLASH UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI ANAK USIA DINI - Puji Yulianti; Sella Oktania (Jurnal Anak Bangsa, 2023)
This study aims to develop Flash-based interactive multimedia for group B children to assist the learning process at TKIT Nusantara Banten. Flash-based interactive multimedia is used to help students master the excretory system material. This research includes research on development related to borg and gall. This product was developed based on original research as a Flash-based interactive multimedia product for group B children in plant subjects. The test subjects in this developmental research were expert subjects, namely excretory system material experts, learning media experts, linguists, as well as a sample of children of all ages. Group B was potential product users. Determination of sample subjects by random sampling method, namely 5 children for the main field experiment and 15 children for the field experiment. Research and development results: (1) The learning material development model takes place in several stages, namely information gathering, product planning that is being developed, initial forms of Flash-based multimedia products, initial field trials, initial modifications of Flash-based multimedia products, main field trials, operational products. assessment, actual activity test, final product evaluation and activity actual test (2) Learning materials can have a positive impact on group B children's learning outcomes if they obtain a score of 76.58% with the "Good" criterion. and student learning motivation is considered strong with a percentage of 80.3%.